Small molecule mimetics of α-helical domain of IRAK2 attenuate the pro-inflammatory effects of IL-33 in asthma-like mouse models - Li, Jinghong (J Immunol, 2018)
Interleukin-33 (IL-33) and its receptor ST2 play important roles in airway inflammation and contribute to asthma onset and exacerbation. IL-33/ST2 signaling pathway recruits adapter protein myeloid differentiation primary response 88 (MyD88) to transduce intracellular signaling. MyD88 forms a complex with interleukin receptor associated kinases (IRAKs), IRAK4 and IRAK2, called the Myddosome (MyD88-IRAK4-IRAK2). Myddosome subsequently activates downstream NF-kB, MAPKs p38 and JNK. We established an asthma-like mouse model by intratracheal administration of IL-33. The IL-33 model has very similar phenotype compared with the ovalbumin (OVA) induced mouse asthma model. The importance of MyD88 in the IL-33/ST2 signaling transduction was demonstrated by the MyD88 knock-out mice were protected from the IL-33 induced asthma. We synthesized small molecule mimetics of the α-helical domain of IRAK2 with drug-like characteristics based on the recent advances in the designing of α-helices compounds. The mimetics can competitively interfere the protein-protein interaction between IRAK2 and IRAK4, leading to disruption of Myddosome formation. A series of small molecules were screened using an NF-kB promoter assay in vitro. The lead compound, 7004, was further studied in the IL-33 induced and OVA induced asthma mouse models in vivo. Compound 7004 can inhibit the IL-33 induced NF-kB activity, disrupt Myddosome formation and attenuate the pro-inflammatory effects in asthma-like models. Our data indicate that the Myddosome may represent a novel intracellular therapeutic target for diseases in which IL-33/ST2 plays important roles, such as asthma and other inflammatory diseases.